Perturbation treadmill training improves clinical characteristics of gait and balance in Parkinson’s disease - Gaßner, Heiko; Steib, Simon; Klamroth, Sarah; Pasluosta, Cristian F.; Adler, Werner; Eskofier, Bjoern M.; Pfeifer, Klaus; Winkler, Jürgen; Klucken, Jochen (Journal of Parkinson's Disease, 2019)
Background: Impaired gait and postural stability are cardinal motor symptoms in Parkinson’s disease (PD). Treadmill training improves gait characteristics in PD. Objective: This study investigates if postural perturbations during treadmill training i